Atelectasis, Shunt, and Worsening Oxygenation Following Reduction of Respiratory Rate in Healthy Pigs Undergoing ECMO: An Experimental Lung Imaging Study - Spinelli, Elena; Colussi, Giulia; Dal Santo, Gaia; Scotti, Eleonora; Marongiu, Ines; Garbelli, Erica; Mazzucco, Alessandra; Dondossola, Daniele; Maia, Raquel; Battistin, Michele; Biancolilli, Osvaldo; Rosso, Lorenzo; et al. (Frontiers in Physiology, 2021)
Introduction: Reducing the respiratory rate during Extracorporeal Membrane Oxygenation (ECMO) decreases the mechanical power but it might induce alveolar de-recruitment. Dissecting de-recruitment due to lung edema vs. the fraction due to hypo-ventilation may be challenging in injured lungs. Objectives: We characterized changes in lung physiology (primary endpoint: development of atelectasis) associated with progressive reduction of the respiratory rate in healthy animals on ECMO. Methods: Six female pigs underwent general anesthesia and volume control ventilation (Baseline: PEEP 5 cmH2O, Vt 10 ml/kg, I:E=1:2, FiO2 0.5, rate 24 bpm). Veno-venous ECMO was started and respiratory rate was progressively reduced to 18, 12 and 6 breaths per minute (six-hour steps), while all other settings remained unchanged. ECMO blood flow was kept constant while gas flow was increased to maintain stable PaCO2. Results: At Baseline (without ECMO) and towards the end of each step, data from quantitative CT scan, Electrical Impedance Tomography and gas exchange were collected. Increasing ECMO gas flow while lowering the respiratory rate was associated with an increase in the fraction of non-aerated tissue (i.e., atelectasis) and with a decrease of tidal ventilation reaching the gravitationally-dependent lung regions (p=0.009 and p=0.018). Intrapulmonary shunt increased (p<0.001) and arterial PaO2 decreased (p<0.001) at lower rates. The fraction of non-aerated lung was correlated with longer expiratory time spent at zero flow (r=0.555, p=0.011). Conclusions: Progressive decrease of respiratory rate coupled with increasing CO2 removal in mechanically ventilated healthy pigs is associated with development of lung atelectasis, higher shunt and poorer oxygenation.